Interface Management for Automating Finite Element Analysis Workflows. Issue 3 (3rd May 2016) - Tierney, Christopher M.; Nolan, Declan C.; Robinson, Trevor T.; Armstrong, Cecil G.
ABSTRACT: This paper outlines the importance of robust interface management for facilitating finite element analysis workflows. Topological equivalences between analysis model representations are identified and maintained in an editable and accessible manner. The model and its interfaces are automatically represented using an analysis-specific cellular decomposition of the 3D design space. Rework of boundary conditions following changes to the design geometry or the analysis idealization can be minimized by tracking interface dependencies. Utilizing this information with the Simulation Intent specified by an analyst, automated decisions can be made to process the interface information required to rebuild analysis models. Through this work automated boundary condition application is realized within multi-component, multi-resolution and multi-fidelity analysis workflows. GRAPHICAL ABSTRACT: